Roles of peroxisome proliferator-activated receptor α in the pathogenesis of ethanol-induced liver disease. (25th August 2020) - Meng, Fan-Ge; Zhang, Xiu-Ning; Liu, Shi-Xuan; Wang, Yi-Ran; Zeng, Tao
Abstract: Alcoholic liver disease (ALD) is a progressively aggravated liver disease with high incidence in alcoholics. Ethanol-induced fat accumulation and the subsequent lipopolysaccharide (LPS)-driven inflammation bring liver from reversible steatosis, to irreversible hepatitis, fibrosis, cirrhosis, and even hepatocellular carcinoma. Peroxisome proliferator-activated receptor α (PPARα) is a member of the nuclear receptor superfamily of ligand-activated transcription factors and plays pivotal roles in the regulation of fatty acid homeostasis as well as the inflammation control in the liver. It has been well documented that PPARα activity and/or expression are downregulated in liver of mice exposed to ethanol, which is thought to be one of the prime contributors to ethanol-induced steatosis, hepatitis and fibrosis. This article summarizes the current evidences from in vitro and animal models for the critical roles of PPARα in the onset and progression of ALD. Importantly, it should be noted that the expression of PPARα in human liver is reported to be similar to that in mice, and PPARα expression is downregulated in the liver of patients with nonalcoholic fatty liver disease (NAFLD), a disease sharing many similarities with ALD. Therefore, clinical trials investigating the expression of PPARα in the liver of ALD patients and the efficacy of strong PPARα agonists for the prevention and treatment of ALD are warranted. Highlights: PPARα plays pivotal roles in regulation of fatty acid homeostasis in liver. PPARα activity and/or expression in liver is downregulated after ethanol exposure. The expression of PPARα in human liver may be similar to that in mice liver. PPARα expression is decreased in the liver of patients with NAFLD.